Health service needs in patients receiving hemodialysis therapy: qualitative study - Yuliani Budiyarti; Evimira Sukanti (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
Quality health services are health services that are provided based on patient needs, not based on what is owned by the service-providing institution. Patients with chronic diseases such as kidney failure undergoing hemodialysis need more supportive nursing care, such as physical and psychological support and information about their condition. This study aims to explore and identify health service needs in patients receiving hemodialysis therapy. This research is qualitative research on phenomenology. Data was collected using semi-structured and in-depth interviews with 17 participants of end-stage renal failure who underwent hemodialysis therapy, selected by purposive sampling. Thematic analysis is used for data analysis. The study found three main themes: services to meet basic needs when hemodialysis therapy was carried out, support received while undergoing hemodialysis therapy, and Various health services that have yet to be received while undergoing hemodialysis therapy. It can be concluded that identifying service needs positively impacts service quality as healthcare workers will better understand patient expectations. Hemodialysis patients have basic physical, psychological, and support needs. Unmet needs include inadequate drug therapy, health workers, and unmet information needs. Healthcare providers should develop strategies to manage these needs, including physical and psychological modification, improvement of facilities, infrastructure, human resources, and interdisciplinary approaches.